Differences in attitudes and behaviors of religious tourists: comparative research between Brazil and Portugal - Campos, Waleska Yone Yamakawa Zavatti; Rodrigues, Maria Carolina Martins; Rosa, Luciana Aparecida Barbieri da; Barbosa, Raul Afonso Pommer; Sousa, Maria Jose; Cohen, Marcos (Revista de Administração da UFSM, 2020)
Purpose – The study aims to explore the particularities of religious tourists’ attitudes and behaviors with different demographic profiles. Therefore, this work aims to verify if there are differences between the attitudes and behaviors of Brazilian and Portuguese religious tourists in terms of gender, nationality, and religiosity. Design/methodology/approach – A survey was carried out with 396 religious tourists residing in Brazil and Portugal, who have visited religious destinations in their country or abroad, to carry out a comparative analysis between groups, according to gender, nationality, and religiosity through Student’s t-test. Findings - The results show significant differences in tourists’ attitudes and behaviors who visit sacred places divided between women and men, Brazilians and Portuguese, and finally, between those who consider themselves religious and non-religious. Research limitations/implications – The study’s limitations involve the use of an instrument with a particularly Christian bias. Practical implications – The practical implications of this study include contributions to improving local infrastructure related to hotels, commerce, and tourist services. Originality/value – From a theoretical perspective, this study contributes to the advancement of administrative sciences as it engenders the intersection between religious tourism and public and non-profit marketing, placing the discussion in two countries with a strong religious tradition in the West, Brazil and Portugal.